Vancomycin-resistant Staphylococcus aureus in Nepal: an impending crisis? - Khanal, B (Nepalese Journal of Ophthalmology, 2012)
DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5878 NEPJOPH 2012; 4(1): 197-198